The acquisition of subject literacy in secondary school CLIL and non-CLIL history education - Sercu, Lies (Frontiers in Education, 2025)
In CLIL (Content and Language Integrated Learning), subject matter content is taught in a foreign language to enhance the learners’ mastery of the foreign language alongside subject matter learning. In previous research, no truly interdisciplinary stance was taken. By contrast, in the investigation reported here, the focus is on the integrated learning of language and content, investigating to what extent students master the characteristics of the genres typical of the subject discipline. Specifically, this article reports a study that, using insights from Systemic Functional Linguistics, investigated to what extent 18-year-old CLIL and non-CLIL students master the genre ‘historical report’ when writing in the CLIL language or in their mother tongue. On the basis of an interdisciplinary analysis of 60 student essays, we found that CLIL and non-CLIL students are equally able to express the voice of the historian in their texts and that overall text quality does not differ substantially between groups. In other words, regardless of the language in which they have studied history as a secondary school subject, they have learned at least to a certain degree to record, appraise, interpret, and evaluate historical facts, figures, and artifacts, just like a trained historian would do.